Relationship between serum cystatin C and diabetic retinopathy in T2DM patients - Gui, Qiuqi; Jiang, Kunhua; Xu, Yuxin (Frontiers in Medicine, 2025)
ObjectiveCystatin C (CysC), as a crucial and sensitive indicator for renal function, has gradually drawn attention for its role in diabetic complications. This study aims to investigate the association between serum CysC levels and diabetic retinopathy (DR).MethodThis cross-sectional study enrolled 818 individuals with type 2 diabetes, including 227 DR patients and 591 patients without DR. All subjects underwent detailed clinical evaluations, including blood glucose, lipid, renal function indicators, and fundus examinations. Logistic regression analyses were applied to assess the correlation between CysC and DR.ResultsThe serum CysC levels in DR patients was significantly higher than those of the controls (p < 0.001). Besides, CysC was negatively correlated with fasting glucose (r = −0.080), TC (r = −0.090), HDL-C (r = −0.107), and albumin (r = −0.222) (all p < 0.05). Compared to the 1st tertile of CysC, the prevalence of DR was increased in the 3rd CysC tertile (OR = 2.14, 95%CI: 1.20–3.82, p = 0.01). This association was more obvious in patients with a long duration of diabetes exceeding 10 years or in non-elderly patients.ConclusionPatients with higher serum CysC levels have an elevated risk of DR in the T2DM population. Future large-scale studies should explore the potential mechanism of CysC in DR and evaluate its potential as a therapeutic target.